Knowledge and Practice Towards Use of Mouthwash Among Dental Practitioners in Chitwan - Shrestha, Erika; Kafle, Shristi; Chaulagain, Rajib (Journal of Karnali Academy of Health Sciences, 2021)
Background: Good oral hygiene has always been an important aspect of total health care. Mouthwashes are chemical formulations used as an adjunct to effectively eliminate the dental plaque. Dental practitioners play a major role in maintenance of good oral hygiene, their opinion over the knowledge, attitude, and practice regarding prescribing mouthwashes is of greater value and significance. The main objective of the study was to assess the dental practitioner’s knowledge of mouthwashes and practice of using mouthwash in Chitwan. Methods: A cross-sectional study was undertaken among the dental practitioners in Chitwan using a selfadministered questionnaire. A total 140 completely filled questionnaires were included in the study. The results were analyzed for descriptive statistics (frequency and percentages) using the SPSS software. Results: Among the 140 participants, majority of them 98(70%) were female. Regarding brands of mouthwash, 40.8 % and 29.3% of the dental practitioners were aware of Chlorhexidine and Listerine mouthwash respectively. Majority of the dental practitioners agreed that mouthwash leave behind extrinsic stains and supragingival calculus. Conclusions: The present study revealed that the dental practitioners have adequate knowledge and excellent practice of using mouthwash. With time the dental practitioners should keep themselves updated.